Covid-19 in the Brazilian stock market - Schiavo, Bruno Andrade (2021)
As Covid-19 ravages through, several researchers have attempted to describe its impact in the share price of listed companies. I investigate the Brazilian stock market through a regression analysis of how three firm characteristics (foreign revenues, cash holdings and leverage) impact share returns across three events of the pandemic in the country. As a result, I show that after the first case of Covid-19 was detected in Brazil, both foreign revenues and leverage had a negative impact on stocks – an increase of one percentage point in foreign revenues is associated with 0.09 decrease in stock returns; an increase of 1 unit of leverage is associated with 13.12 decrease in stocks returns. This negative impact of leverage lingered even after confirmation of community transmission of the virus - an increase of 1 unit of leverage is associated with 17.39 decrease in stocks returns. Interestingly, however, cash holdings did not affect stock returns during the pandemic.